Measuring renewable energy: Evidence from subjective well-being data - Charlotte von Möllendorff; Heinz Welsch (University of Oldenburg, Department of Economics, 2014)
Electricity from renewable sources avoids the disadvantages of conventional power generation (air pollution, greenhouse gases, nuclear risk) but often meets with local resistance due to visual, acoustic, and odor nuisance. We use representative panel data on the subjective well-being of 36,475 individuals in Germany, 1994-2012, for identifying and valuing the local externalities from wind, solar and biomass plants. While the well-being effects of wind turbines refer mainly to initial installations and tend to dissipate over time, the effects of solar and biomass plants build up gradually as their number and capacity rises. In a spatial perspective, power generation from biomass creates negative spillovers to adjacent localities that are absent in the case of wind power.
Keywords: Q42; D62; I31; Q51; 330; renewable energy; local externality; subjective well-being; life satisfaction; nonmarket valuation